A Study on Influence of Sensitivity Analysis on Normalization Techniques by Applying Equal and Exchange of Weight Metrics - Lakshmi, T. Miranda; Martin, A; Venkatesan, V. Prasanna (International Journal of Computer Sciences and Engineering, 2025)
Sensitivity analysis is used to find the robustness of a normalization technique. It is applied in two ways, one by applying equal weights to all the criteria (MSA_EQ) and other by exchanging of weights (MSA_EX). The result obtained for sensitivity analysis when it is conducted with equal weight is described in this paper. The impact of sensitivity analysis on assigning equal weights to criteria is described with different shaded colours for each of the normalization technique. The change in ranking order of the alternatives before and after of sensitivity analysis is described with shaded colour. In this analysis, linear max min normalization has minimum number of altered ranking order for alternatives. In both of these analysis (assigning equal weight to the criteria and exchanging weight of the criteria), selected six normalization techniques maintains different number of alterations in ranking order of alternatives.